An Empirical Investigation to Enhancing Construction Site Performance Through Efficient Material Waste Mitigation in the Malaysian Construction Industry - Abdullah Abkar, Mahdi Mohammed; Yunus, Riduan; Ahmed Saleh Ahmed Saif Al-Shameri,; Ahmed Harouache, (International Journal of Sustainable Construction Engineering and Technology, 2023)
Automation Technological advancements in construction significantly enhance efficiency by integrating productivity, cost-effectiveness, and innovation throughout the construction life cycle, fostering both economic growth and industry advancement. This study investigates the role of Technology and Management Practices TMP in mitigating material waste to enhance Construction Site Performance (CSP) within Malaysia's construction sector. Five hypotheses were formulated to explore the relationship between TMP and CSP. Data collection involved an online survey targeting construction personnel and experts in Malaysia, resulting in 295 valid responses for hypothesis validation. The analysis utilized Partial Least Squares-Structural Equation Modeling (PLS-SEM) techniques in conjunction with IBM's Statistical Package for the Social Sciences (SPSS), recognized for its robust statistical capabilities in empirical research. The study's findings suggest that adopting TMP, along with their perceived value and applicability in material waste mitigation, can notably elevate the performance of Malaysian construction sites. This emphasizes the significance of technology and management practices in workplace strategies. The results imply that all stakeholders can leverage TMP to advance ongoing efforts in reducing material waste, shaping a more sustainable future.